Optical Properties of Indium Doeped ZnO Nanowires - Tsung-Shine Ko; Sin-Liang Ou; Kuo-Sheng Kao; Tz-Min Yang; Der-Yuh Lin (International Journal of Photoenergy)
We report the synthesis of the ZnO nanowires (NWs) with different indium concentrations by using the thermal evaporation method. The gold nanoparticles were used as the catalyst and were dispersed on the silicon wafer to facilitate the growth of the ZnO NWs. High resolution transmission electron microscopy confirms that the ZnO NWs growth relied on vapor-liquid-solid mechanism and energy dispersion spectrum detects the atomic percentages of indium in ZnO NWs. Scanning electron microscopy shows that the diameters of pure ZnO NWs range from 20 to 30 nm and the diameters of ZnO:In were increased to 50–80 nm with increasing indium doping level. X-ray diffraction results point out that the crystal quality of the ZnO NWs was worse with doping higher indium concentration. Photoluminescence (PL) study of the ZnO NWs exhibited main photoemission at 380 nm due to the recombination of excitons in near-band-edge (NBE). In addition, PL results also indicate the slightly blue shift and PL intensity decreasing of NBE emission from the ZnO NWs with higher indium concentrations could be attributed to more donor-induced trap center generations.